Efficient Water Resource Allocation: CASO Approach for Networking Reservoirs - Suwapat Kosasaeng; Anongrit Kangrang (Advances and Challenges in Science and Technology Vol. 9, 2023)
The goal of this chapter was to apply conditional atom search optimization (CASO) for searching optimum rule curves of a networking reservoirs system with a reservoir simulation model, consisting of five reservoirs and to compare the situation of water excess using optimum rule curves from the CASO technique and a conditional genetic algorithm (CGA). Water resources provide value to individuals, ecosystems, farms, firms, and society in various ways – from the ecological value provided by supporting key species, to the economic value derived from productive uses, to the existence value of iconic lakes or rivers. The networking reservoirs system consisted of 5 reservoirs located in Sakon Nakhon Province, Thailand. A CASO was used to look for the network reservoir system’s best rule curves, and the best rule curves were found. The optimum rule curves were made so they could be compared to the optimum rule curves of CGA for both a single reservoir and a network of reservoirs. A comparison of the operating systems of a single reservoir and a networking reservoirs system was used to ascertain the efficiency of the new optimum rule curves. The findings showed both abundant and scarce water conditions. where frequency and duration are the conditions of shortage. Whilst, excesses of water are average water and the highest water. In addition, the efficiency of searching for optimum rule curves was compared between conditional genetic algorithm (CGA) and CASO techniques. The new optimum rule curves from the networking reservoirs system had an average excess water of 43.828 MCM/year. This average excess water was less than that found for optimum curves from the single system in which the average excess of water was 45.602 MCM/year. CASO was 40.00% more efficient than CGA in converging optimal rule-curve solutions. The results showed that the optimum rule curves from considering the networking reservoirs system can reduce the among of excess water entering the last downstream reservoir, Huay Sai Kamin. A downstream reservoir analysis was done for the networking reservoirs system, which used water from the upstream reservoirs. The outcomes shown that, in comparison to a single reservoir system, the optimal rule curves employing CASO operated as a networking reservoirs system offered improved efficiency. Furthermore, they cut the duration of time that water was over the river’s capacity at a downstream weir from two months to one month.